The impact of fertilization on ammonia-oxidizing bacteria and comammox Nitrospira communities and the subsequent effect on N2O emission and maize yield in a semi-arid region - Fudjoe, Setor Kwami; Li, Lingling; Anwar, Sumera; Shi, Shangli; Xie, Junhong; Yeboah, Frederick Kwame; Wang, Linlin (Frontiers in Microbiology, 2023)
The control of nitrous oxide (N2O) emissions through nitrification and the optimization of maize yield are important in agricultural systems. However, within the semi-arid region, the impact of fertilization on the function of nitrification communities and its connection with N2O emissions in the rhizosphere soil is still unclear. Our study investigates the influence of fertilization treatments on the communities of ammonia-oxidizing bacteria (AOB) and the complete ammonia oxidizers of the Nitrospira known as comammox (CAOB) in a maize agroecosystem. Nitrous oxide production, potential nitrification activity (PNA), maize yield, and nitrogen use efficiency (NUE) were determined for the same samples. The fertilizer treatments included a control group without fertilization (NA), inorganic fertilizer (CF), organic fertilizer (SM), combined inorganic and organic fertilizer (SC), and maize straw (MS). The SC treatment indicated a lower cumulative N2O emission than the CF treatment in the 2020 and 2021 cropping seasons. The AOB community under the CF, MS, and SM treatments was predominantly composed of Nitrosospira cluster 3b, while the SC treatment was associated with the comammox Nitrospira clade A.1 lineage, related to key species such as Ca. Nitrospira inopinata and Ca. Nitrospira nitrificans. Network analysis demonstrated a positive potential for competitive interaction between hub taxonomy and distinct keystone taxa among AOB and comammox Nitrospira nitrifiers. The structural equation model further revealed a significant positive association between AOB nitrifiers and N2O emission, PNA, soil pH, SOC, NO3−-N, and DON under organic fertilization. The keystone taxa in the comammox Nitrospira nitrifier and network Module II exhibited a positive correlation with maize productivity and NUE, likely due to their functional activities stimulated by the SC treatment. It is noteworthy that the AOB community played a more significant role in driving nitrification compared to the composition of comammox Nitrospira. Collectively, combined inorganic and organic fertilizer (SC) treatment exhibits high potential for reducing N2O emissions, enhancing maize productivity, increasing NUE, and increasing the sustainability of the nitrogen dynamics of maize agroecosystems in the semi-arid Loess Plateau.